IDENTIFIKASI KOMPONEN PENYUSUN ASAP CAIR DARI AMPAS SAGU DAN KULIT BATANG TANAMAN SAGU (Metroxylon sagu Rottb) SERTA PENENTUAN SENYAWA FENOLAT TOTAL DAN AKTIVITAS ANTIOKSIDAN - Aditria, Riswandi (Chem Info Journal, 2013)
Liquid smoke is one or the other material which had depeloved as food recently. Potential of liquid smoke as preservatives very influence by its antioxidant activity that caused by phenol and its derivates content. In this research sago waste and sago palm stem shell had processed to be liquid smoke. Activity as foodstuffs preservation very strong correlation with indicator of it composer structure, total phenolic compounds, and antioxidant activity. Liquid smoke from sago waste had succeed obtained with yield 33% and liquid smoke from sago palm stem shell 44%. GCMS data is show existence some compounds with carbonyl group and phenolic, 10 compound had obtained which possess index similarity minimum 80% with reference compounds. Total phenolic compounds for sago waste and sago palm stem shell is 130.59 and 105.30 mg/g liquid smoke equivalent galic acid, respectively. Antioxidant activity test had obtained IC50 number is 303.63 mg/L at sago waste ligid smoke and 442.45 mg/L at sago palm stem shell. Liquid smoke from sago waste and sago palm stem shell have antioxidant activity that un potential, so that must existence more depeloving.